2013
DOI: 10.1007/s10930-013-9536-8
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Antioxidant Peptides from Leukocyte Extract of Crocodylus siamensis

Abstract: Antioxidant peptides were isolated from the leukocyte extract of the Siamese crocodile, Crocodylus siamensis. Crocodile leukocyte was extracted by a combination of methods including freeze-thawing, acetic acid extraction and homogenization. The peptides in the leukocyte extract were purified by anion exchange chromatography and reversed phase-high performance liquid chromatography. The 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay was used to evaluate the antioxidant activity of the elution pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…This is consistent with previous reports that reported that the activities of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) were increased in the human lymphocytes when induced by oxidative stress [29]. Another indication about the peptides in crude leukocyte extracts from C. siamensis as described by Theansungnoen et al [30], who reported the antioxidant activity was observed in two peptides i.e. TDVLGLPAK (912.5 Da) and DPNAALPAGPR (1,148.6 Da).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous reports that reported that the activities of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) were increased in the human lymphocytes when induced by oxidative stress [29]. Another indication about the peptides in crude leukocyte extracts from C. siamensis as described by Theansungnoen et al [30], who reported the antioxidant activity was observed in two peptides i.e. TDVLGLPAK (912.5 Da) and DPNAALPAGPR (1,148.6 Da).…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that hosts that receive DLE can generate a well-directed immune response against pathogens such as T. gondii, which are susceptible to the effects of the TH1 immune response. This immune response involves pro-inflammatory cytokines, IFN-g, activated macrophages and related events such as the release of oxygen and nitrogen metabolism products, which may decrease parasite replication ( Merchant et al 2006 , Gaddi & Yap 2007 , Franco-Molina et al 2008 , Thammasirirak et al 2014 , Theansungnoen et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dialyzable leukocyte extracts (DLE), or transfer factors, are defined as immunomodulatory molecules with molecular weights of approximately 10 kDa; they are derived from individuals sensitised to a particular antigen and have the property of transferring specific cell-mediated immunity to individual recipients ( Lawrence 1955 , Kirkpatrick 2000 ). Leukocyte extracts are commercially sold and can be obtained from human blood ( Espinosa-Padilla et al 2009 ), bovine dialyzable leukocyte extract and bovine colostrum ( Sánchez-González et al 2011 ), egg yolk ( Xu et al 2006 ), and crocodile spleen ( Merchant et al 2006 , Theansungnoen et al 2014 ). In research laboratories, these extracts are obtained from mice exposed to specific antigens ( Fabre et al 2004 ).…”
mentioning
confidence: 99%
“…This animal is smaller than the alligator, typically about 7 ft long and 80–150 lbs when fully grown, although larger specimens have been recorded [4]. These animals are being intensively studied as part of their conservation, and are bred in captivity, and thus are accessible to researchers for DNA or blood samples [58,59,60]. …”
Section: Four Orders Of Reptilesmentioning
confidence: 99%